Customer-Perceived Value in Creating Customer Satisfaction and Revisit Intention in Sharia Hotels - Fitranty Adirestuty (Bank Indonesia, 2019)
The purpose of this study was to identify the relationship between Islamic service quality, Muslim Customer Perceived Value (MCPV), customer satisfaction, and revisit intention on sharia hotels in Bandung. A systematic random sampling was used to draw sample of 255 customers. The hotel includes Orange Home Sharia, Sharia Narapati Hotel, Cottage Daarul Jannah, Daarul Mutmainah, and MQ Guest House. This research used Structural Equation Modeling to measure the variables of service quality (Gayatri, 2013) and Muslims Customer Perceived Value (MCPV) (Eid and Gohary, 2015) to measure the perceived value variables. Eleven hypotheses were developed and tested using a sample of 255 Muslim tourists. Exploratory and confirmatory factor analysis was used to test the validity of the measures, while the structural equation modeling in hypotheses testing. The strength of the relationship between the constructs indicates that features of the suggested MCPV model are crucial to achieving Muslim customer retention in the tourism industry. Findings also suggest that the availability of the suggested Islamic attributes value, along with conventional value dimensions, could satisfy Muslim tourists when they buy a tourism package.